2021
DOI: 10.3389/fimmu.2021.639008
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Cellular Prion Protein Induces Neuronal Type 2-Like Hypersensitivity

Abstract: BackgroundPrevious reports identified proteins associated with ‘apoptosis’ following cross-linking PrPC with motif-specific anti-PrP antibodies in vivo and in vitro. The molecular mechanisms underlying this IgG-mediated neurotoxicity and the role of the activated proteins in the apoptotic pathways leading to neuronal death has not been properly defined. Previous reports implicated a number of proteins, including apolipoprotein E, cytoplasmic phospholipase A2, prostaglandin and calpain with anti-PrP antibody-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 144 publications
(223 reference statements)
0
15
0
Order By: Relevance
“…This confirms that the activation of neurons only or simultaneous activation of both neurons and microglia following treatment with anti-Aβ antibody leads to increased TNF-α expression while activation of microglia only following anti-Aβ antibody treatment before coculture with neurons leads to decreased TNF-α expression. Of interest, in a previous study, we did not find significant expression of TNF-α when we co-cultured the anti-PrP antibody-treated microglia with mouse primary neurons (Adhikari et al, 2021a). TNF-α is considered as a key mediator of the atopic allergy inflammation (Ying et al, 1991), human lung allergic reactions (Casale et al, 1996), and allergic rhinitis (Iwasaki et al, 2003;Mo et al, 2011) highlighting its association with hypersensitivity responses.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This confirms that the activation of neurons only or simultaneous activation of both neurons and microglia following treatment with anti-Aβ antibody leads to increased TNF-α expression while activation of microglia only following anti-Aβ antibody treatment before coculture with neurons leads to decreased TNF-α expression. Of interest, in a previous study, we did not find significant expression of TNF-α when we co-cultured the anti-PrP antibody-treated microglia with mouse primary neurons (Adhikari et al, 2021a). TNF-α is considered as a key mediator of the atopic allergy inflammation (Ying et al, 1991), human lung allergic reactions (Casale et al, 1996), and allergic rhinitis (Iwasaki et al, 2003;Mo et al, 2011) highlighting its association with hypersensitivity responses.…”
Section: Discussionmentioning
confidence: 89%
“…We have previously shown that treatment of neuronal cell lines with anti-PrP monoclonal antibodies leads to a hypersensitivity-like reaction (Adhikari et al, 2021a). We wanted to investigate whether the 18 common allergy related proteins were involved in a type 1 and/or 2 hypersensitivity reaction.…”
Section: Anti-aβ Antibodies Cause Neuronal Hypersensitivity-like and ...mentioning
confidence: 99%
See 3 more Smart Citations